POSTERS Trans-18:1 isomer profiling in French processed foods containing partially hydrogenated vegetable oils - Destaillats Frédéric; Prechth Dietz; Molkentin Joachim; Wolff Robert L. (Oléagineux, Corps gras, Lipides, 2000)
* FD is an ISTAB student engineer funded by an Adera grant for his training period at the Bundesanstatt für Milchforschung